Transformation of Gig Economy Labor Structures: Implications for Social Security Accounting and New Economic Vulnerability Risks - Delila Rambe (CV. Get Press Indonesia, 2026)
The global labor market is experiencing a profound metamorphosis due to the rapid expansion of digital platforms, which challenges traditional employment paradigms and social protection frameworks. This study investigates the transformation of gig economy labor structures and its specific implications for social security accounting and emerging economic vulnerability risks. Utilizing a quantitative design with an ex post facto approach, the research analyzes a weighted sample of 2,185,340 individuals from the Indonesian National Labor Force Survey (Sakernas) and BPJS Ketenagakerjaan datasets across major metropolitan areas, including Jakarta and Surabaya. Variables examined include algorithmic management intensity, contribution persistence, and the precarity index. Results indicate that while platforms offer